Building marketing culture and reflection on the mental image Search for a pilot sample of managers in the General Company for Vegetable Oil Industry - عذيب, عامر فدعوس; سعيد, هدى قاسم (Journal of Economics and Administrative Sciences, 2017)
The subject of marketing culture and mental image is one of the important topics in the field of management. There is no study that combines these two variables. The research is important because of the increasing importance of the subject. The future direction of the company in question will support the company's economic and marketing responsibilities. And reflect the company's mental image, as a culture that contributes to changing the reality of the organization investigated by polling the views of a sample of managers in the General Company for Vegetable Oil Industry, which (30) out of the (65) individual, and There are two hypotheses of research: There is a significant correlation between marketing culture and mental image. There is a significant effect of marketing culture in the mental picture. The questionnaire is a main tool for collecting data and information. The questionnaire was analyzed using SPSS in data entry and analysis. And the standard deviations and regression coefficients, and the research reached a number of conclusions through the averages of the sample answers. The most prominent of these: There is a marketing culture in the company investigated through the clarity and existence of sub-variables of the research, The elements of marketing culture affect the mental image represented by quality of service, sales mission, personal relations, organization, internal communication and innovation for marketing culture, company image, trust in the company, commitment to the company and recommendation of the company towards others. It recommends research work to overcome problems and work to remove them through the dissemination of marketing culture and its role in changing the mental image of the company and similar companies and distinguished and use my own information system Able to collect data and constantly updated to support the senior management information to enhance the status of attention and achieving goals.  President of the search terms: marketing culture, mental image, quality of service and important selling personal relationships and organization, internal communication and innovation, the company's image and confidence in the company and commitment to the company and to recommend the company to others .